2021
DOI: 10.1021/acs.jafc.1c05024
|View full text |Cite
|
Sign up to set email alerts
|

Biotransformation and Quantification of Sinensetin and Its Metabolites in Plasma, Urine, and Feces of Rats

Abstract: As one of the major polymethoxyflavones in citrus peels, sinensetin (Sin) has been reported to possess numerous bioactivities. However, its detailed in vivo metabolic fate has not been uncovered yet. In the present study, the possible metabolites of Sin were synthesized, and all five mono-demethylated metabolites were successfully identified via ultraperformance liquid chromatography−tandem mass spectrometry (UPLC−MS/MS) analysis in rats fed with 100 mg/(kg•bw) Sin. The excretion and pharmacokinetic studies we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
23
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(29 citation statements)
references
References 18 publications
(25 reference statements)
5
23
1
Order By: Relevance
“…Obviously, the results of the two studies are far apart, which may be related to the different extraction methods and concentration and purity, but at least provide a hint that SIN can be obtained through dietary intake. Finally, it is worth mentioning that according to excretion and pharmacokinetic studies, SIN is easily absorbed in the small intestine, 42 which is also conducive to the effect of oral drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Obviously, the results of the two studies are far apart, which may be related to the different extraction methods and concentration and purity, but at least provide a hint that SIN can be obtained through dietary intake. Finally, it is worth mentioning that according to excretion and pharmacokinetic studies, SIN is easily absorbed in the small intestine, 42 which is also conducive to the effect of oral drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the structural resemblance of 5-OH Sin and another 5-OH citrus PMF, 5-demethylnobiletin, the potential major metabolites of 5-OH Sin were synthesized based on the result of identified 5-demethylnobiletin metabolites . As illustrated in Figure , in total six compounds were quantified in the LC-MS/MS analysis, among which four compounds have been reported in our previous study, regarding the in vivo metabolism of Sin. The remaining two compounds, namely, 5,3′-didemethylsinensetin (5,3′-diOH Sin) and 5,4′-didemethylsinensetin (5,4′-diOH Sin), are generally known as eupatorin and cirsilineol, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The metabolism of Sin in urine, feces, and plasma of rats after oral administration was therefore discussed. The results indicated that little amount of 5-demethylsinensetin (5-OH Sin) was metabolized from Sin in either conjugated or free forms in the host body . Based on this finding, it can be intriguing and important to figure out the actual metabolic fate of 5-OH Sin, which is the most unique monodemethylated metabolite of Sin with the lowest polarity, and how it is different from its parent compound, Sin.…”
Section: Introductionmentioning
confidence: 99%
“…As illustrated in Figure 4, the synthetic pathways of B-ring demethylated sinensetin, i.e. 3′demethylsinensetin (16a), 4′-demethylsinensetin (16b) and potential 3′,4′-didemethylsinensetin (16c) was nearly the same except using different benzaldehydes without (Wang et al, 2021) or with a benzyl protected group at 3-or 4-postion, or 3,4-dibenzyl protection (Li et al, 2006;Li et al, 2007).…”
Section: Synthesis Of 5-demethylsinensetinmentioning
confidence: 98%
“…In the 2-step synthetic scheme (Figure 4A) (Wang et al, 2021), a direct condensation between 6-hydroxy-2,3,4-trimethoxyacetophenone ( 10) and 3-hydroxy-4methoxybenzylaldehyde (14a) or 4-hydroxy-3-methoxybenzaldehyde (14b) generated a chalcone (15a or 15b), followed by simultaneous cyclization and oxidation to yield 3′-demethylsinensetin (16a) or 4′-demethylsinensetin (16b), which is straightforward and convenient.…”
Section: Synthesis Of 5-demethylsinensetinmentioning
confidence: 99%